Molecular Evolution and Organization of Ribosomal DNA in the Hawkweed Tribe Hieraciinae (Cichorieae, Asteraceae) - Fehrer, Judith; Slavíková, Renáta; Paštová, Ladislava; Josefiová, Jiřina; Mráz, Patrik; Chrtek, Jindřich; Bertrand, Yann J. K. (Frontiers in Plant Science, 2021)
Molecular evolution of ribosomal DNA can be highly dynamic. Hundreds to thousands of copies in the genome are subject to concerted evolution, which homogenizes sequence variants to different degrees. If well homogenized, sequences are suitable for phylogeny reconstruction; if not, sequence polymorphism has to be handled appropriately. Here we investigate noncoding rDNA sequences (ITS/ETS, 5S-NTS) along with the chromosomal organization of their respective loci (45S and 5S rDNA) in diploids of the Hieraciinae. The subtribe consists of genera Hieracium, Pilosella, Andryala and Hispidella and has a complex evolutionary history characterized by ancient intergeneric hybridization, allele sharing among species, and incomplete lineage sorting. Direct or cloned Sanger sequences and phased alleles derived from Illumina genome sequencing were subjected to phylogenetic analyses. Patterns of homogenization and tree topologies based on the three regions were compared. In contrast to most other plant groups, 5S-NTS sequences were generally better homogenized than ITS and ETS sequences. A novel case of ancient intergeneric hybridization between Hispidella and Hieracium was inferred, and some further incongruences between the trees were found, suggesting independent evolution of these regions. In some species, homogenization of ITS/ETS and 5S-NTS sequences proceeded in different directions although the 5S rDNA locus always occurred on the same chromosome with one 45S rDNA locus. The ancestral rDNA organization in the Hieraciinae comprised 4 loci of 45S rDNA in terminal positions and 2 loci of 5S rDNA in interstitial positions per diploid genome. In Hieracium, some deviations from this general pattern were found (3, 6, or 7 loci of 45S rDNA; 3 loci of 5S rDNA). Some of these deviations concerned intraspecific variation, and most of them occurred at the tips of the tree or independently in different lineages. This indicates that the organization of rDNA loci is more dynamic than the evolution of sequences contained in them and that locus number is therefore largely unsuitable to inform about species relationships in Hieracium. No consistent differences in the degree of sequence homogenization and the number of 45S rDNA loci were found, suggesting interlocus concerted evolution.